Progress on the Total Synthesis of the Heptasaccharide Fragment Present in the Antibacterial Agent Saccharomicin B. - Bylsma, Marissa. (Tufts University. Tisch Library., 2019)
Antimicrobial resistance is becoming a major health crisis, with the number of lethal infections associated with drug-resistant bacteria pathogens rapidly increasing. Unfortunately, currently used antibiotics are starting to become ineffective against these resistant strains without any new classes of antibiotics in the pipeline. One way to solve this problem is through the reinvestigation of previously isolated natural products. Our focus will be placed on the saccharomicin natural products, which exhibit moderate to excellent activity against Gram-positive and Gram-negative pathogens. Regrettably, the saccharomicins are currently not marketable drugs due to their high toxicity and narrow therapeutic window. Chapter 1 highlights three approaches that can be used for producing the saccharomicins: biological isolation, chemoenzymatic and chemical synthesis. We imagined saccharomicin B can be chemically synthesized through a [6+4+7] convergent approach by linking monosaccharides together through glycosylation reactions. This thesis will be focused on the synthesis of the heptasaccharide (Sac-7-Fuc-1) fragment. In the saccharomicins, there are five monosaccharides: D-saccharosamine (Sac), D-fucose (Fuc), L-rhamnose (Rha), L-digitoxose (Dig) and L-epi-vancosamine (Epi). Previously developed approaches for synthesizing the Sac monosaccharide as well as the Fuc-aglycone and Fuc-Sac-Dig trisaccharide fragments in saccharomicin B will be detailed in Chapter 1. We will also focus on glycosylation reactions using 2-deoxy sugars that have been applied towards the total synthesis of natural products. Lastly, our reagent-controlled dehydrative glycosylation reactions and their potential applicability towards the synthesis of the Sac β-linkages in saccharomicin B will be described. Chapter 2 will highlight synthetic routes developed for constructing the Rha, Fuc and Sac monosaccharides as well as the aglycone unit required for heptasaccharide construction. An alternative synthetic route for Sac starting from carbohydrate starting materials will also be described. Chapters 3 and 4 will highlight the synthetic routes of the tri- and tetrasaccharide fragments necessary for heptasaccharide synthesis (Sac-7-Fuc-1). Glycosylation optimizations for synthesizing the β-linked Sac-Rha and Sac-Fuc disaccharides will be explained, as well as construction of the final fragment targets. It is anticipated with these two oligosaccharides, the final heptasaccharide target can be constructed through a [3+4] convergent synthesis.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Chemistry.; Advisor: Clay Bennett.; Committee: Samuel Thomas, Krishna Kumar, and Isaac Krauss.; Keywords: Chemistry, and Organic chemistry.